EFEKTIVITAS PELAYANAN REEKSPOR BARANG IMPOR DALAM MENINGKATKAN KEPATUHAN KEPABEANAN DI KANTOR PELAYANAN UTAMA BEA DAN CUKAI TIPE A TANJUNG PRIOK TAHUN 2023 – 2024 - Ahmad Dhabith Jihaduddin Shabran; Citra Novlyani (Jurnal Ilmu Administrasi Publik, 2026)
Re-export services for imported goods constitute a customs instrument used to handle imported goods that do not comply with prevailing regulations, particularly those related to prohibitions and restrictions. In practice, a notable phenomenon at the Type A Main Customs and Excise Office of Tanjung Priok is the increase in re-export service activities accompanied by fluctuations in customs enforcement cases. This condition indicates that re-export services function not only as an administrative mechanism but are also closely linked to supervision and the development of customs compliance among service users. This study aims to analyze the effectiveness of imported goods re-export services in enhancing customs compliance at the Type A Main Customs and Excise Office of Tanjung Priok during the 2023–2024 period. The research employs a qualitative approach, with data collected through in-depth interviews, observation, and document analysis. The analysis of effectiveness is based on Duncan’s organizational effectiveness theory, which comprises goal achievement, integration, and adaptation indicators. The findings indicate that re-export services have been implemented with a reasonable level of effectiveness in gradually improving customs compliance. However, the effectiveness has not yet been fully optimal due to administrative constraints, suboptimal inter-agency integration, and varying levels of readiness among service users in adapting to regulatory and system changes. Therefore, strengthening inter-agency integration, enhancing user compliance guidance, and optimizing re-export service systems are necessary. Keywords Service Effectiveness, Re-Export Services, Customs Compliance, Customs and Excise, Tanjung Priok.